2016
DOI: 10.3892/mmr.2016.4995
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b inhibits the proliferation of hepatocellular carcinoma by targeting DNA methyltransferase 3a

Abstract: Aberrant microRNA (miRNA or miR) expression has been reported to contribute to the pathogenesis of hepatocellular carcinoma (HCC). However, the involvement of specific miRNAs in HCC remains to be elucidated. The present study aimed to investigate the potential role of miR-200b and the mechanism underlying its function in hepatocarcinogenesis. The results of the present study demonstrated that the expression levels of miR‑200b were significantly reduced in HCC tissue samples, as compared with normal liver (NL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…6C and D). MiR-200b has been reported to suppress cell proliferation in several cell lines22232425. Thus, we propose that miRNA-200b-3p may also be involved in the regulation of the proliferative effect of TSCs.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…6C and D). MiR-200b has been reported to suppress cell proliferation in several cell lines22232425. Thus, we propose that miRNA-200b-3p may also be involved in the regulation of the proliferative effect of TSCs.…”
Section: Resultsmentioning
confidence: 78%
“…Microarray analysis and qRT-PCR revealed the difference in miRNA-200b-3p between TSCs and MSCs. Recent reports indicated that miRNA-200b is highly correlated with cell proliferation222425. Especially, in cardiac cell lines, Yao et al 31.…”
Section: Discussionmentioning
confidence: 99%
“…Its elevated expression was observed in gastric cancer as well [10]. Its role has also been established in the development of hepatocellular carcinoma (HCC) -inhibition of DNMT3a expression by microRNA miR-200b causes decrease in tumour proliferative activity [11]. On the other hand, the expression of DNMT3a is up-regulated by coexisting hepatitis B virus (HBV) infection [12], which is one of the main risk factor for development of HCC with the significant exception of fibrolamellar variant.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs, miRs) are short noncoding RNAs that can modulate the expression of target messenger RNAs (mRNAs). They have been demonstrated to be dysregulated in experimental and human HCC and have emerged as promising disease biomarkers because of their stability and sequence homology between species, especially in mammals . MicroRNAs can be detected in the circulation .…”
Section: Introductionmentioning
confidence: 99%
“…They have been demonstrated to be dysregulated in experimental and human HCC and have emerged as promising disease biomarkers because of their stability and sequence homology between species, especially in mammals. [8][9][10][11][12][13][14] MicroRNAs can be detected in the circulation. 15,16 Studies have identified a variety of miRNAs that differentiate HCC patients from healthy controls.…”
mentioning
confidence: 99%